Kekuatan Hukum Kantor Pajak Sebagai Kreditor Pemohon Pernyataan Pailit - Andani, Devi; Murjiyanto, R; Ariyani, Nita; Muhoiyaroh, Nur (Kertha Patrika; Vol 46 No 1 (2024), 2024)
This study aims to examine and determine the legal power of the tax office as a creditor of the applicant for a bankruptcy declaration, as well as the legal consequences of the legal power of the tax office as a creditor of the applicant for a bankruptcy declaration. This research is a type of qualitative research that follows the typology of normative legal research. The results of this study show that: first, tax debts have the possibility of being asked for repayment from taxpayers through the bankruptcy declaration application mechanism so that the Tax Office as a creditor in the bankruptcy declaration application has permanent legal force. Second, the Tax Office as a creditor of the applicant for a bankruptcy declaration has the legal consequence that the process of a bankruptcy application submitted by the Tax Office as a debtor is possible. So for creditors who have debts in the form of taxes, the Tax Office as debtor can submit a request for bankruptcy proceedings. Thus, tax debts have the possibility of being asked for repayment by taxpayers through the mechanism of requesting a bankruptcy declaration.